Development of a Digital Assessment Instrument for Professional Bridal Bun Practices Based on Multidimensional Item Response Theory (MIRT) Integrated with the Theory of Conservation of Indonesian Family Cultural Values - Josua, Dian Pertiwi; Siregar, Jenny Sista; Sarifah, Iva; Tjalla, Awaluddin; Mahdiyah; Margono, Gaguk (LPPM Universitas Negeri Jakarta, 2025)
This study developed a digital instrument to assess professional bridal bun practices, employing a method that evaluates multiple competencies simultaneously and is grounded in the preservation of Indonesian family cultural values. The study involved 120 participants, including cosmetology graduates and freelance makeup artists, who piloted a 30-item instrument that covered technical proficiency, visual aesthetics, and cultural values. The analysis demonstrated how effectively questions differentiated between different skill levels, with test scores indicating that the tool performed well in terms of both difficulty and quality. Expert reviews confirmed that the tool could fully measure technical, cultural, and ethical aspects of bridal hairstyling and that it helps share Indonesian family values. The finalized digital tool can serve educational and examination purposes in vocational schools. Overall, this study introduces a culturally relevant and accessible assessment instrument for vocational cosmetology, establishing competency standards, ensuring quality assurance, and preserving local traditions within the contemporary beauty sector. The primary limitations include a small participant pool and a focus on Indonesian values, necessitating further research with a broader cultural and temporal scope.